2021
DOI: 10.1097/pgp.0000000000000791
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Reporting of Endometrial Biopsies From Women on Progestogen Therapy for Endometrial Atypical Hyperplasia/Endometrioid Carcinoma

Abstract: Histologic assessment of response to progestogen therapy is a cornerstone of nonsurgical management of atypical hyperplasia/low-grade endometrioid carcinoma. Pathologists are required to assess whether there is ongoing preneoplastic or neoplastic change in the biopsies (often multiple) taken during therapy. There have been few studies documenting the specific histologic changes induced by therapeutic progestogens and currently there are no guidelines on terminology used in this scenario. Given the need for uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Accurately quantifying the extent of interobserver variation is a difficult process, and it is possible that the high levels of interobserver variability in the included studies could in part be explained by the study protocols. These protocols are not reflective of typical, everyday working practices where prior and additional endometrial biopsies can be reviewed, clinical (including patient age) and radiological information is accessible, and colleagues can be consulted [ 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurately quantifying the extent of interobserver variation is a difficult process, and it is possible that the high levels of interobserver variability in the included studies could in part be explained by the study protocols. These protocols are not reflective of typical, everyday working practices where prior and additional endometrial biopsies can be reviewed, clinical (including patient age) and radiological information is accessible, and colleagues can be consulted [ 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, further research is warranted to determine the applicability of this panel in the diagnostic setting for EH. Interestingly, in a recently conducted international survey of pathologist working practices in the diagnosis of post-hormonal therapy EH specimens, 76% of 95 responding pathologists reported that they never undertook immunohistochemical staining [ 32 ]. This is despite significant advancements in the field regarding the immunohistochemical profile of EH, including proposed biomarker panels for the diagnosis of atypical hyperplasia/EIN [ 38 ].…”
Section: Discussionmentioning
confidence: 99%